PELAYANAN ADMINISTRASI DI KELURAHAN BAMBU PEMALI KABUPATEN MERAUKE - Wa Ode Sitti Mardiana; Eko Rahmat Saputro; Cornelia Evelin Cabui (PAPSEL Research and Consulting, 2024)
Abstract Bambu Pamali Village is one of the agencies in providing services to the community. Service is defined as a result/achievement by a person or group of people with efforts and abilities carried out in fulfilling the wishes and needs of the community in order to increase community satisfaction. The purpose of this study is to determine the quality of service at the Bambu Pemali village office, Merauke Regency. The method used is a qualitative research method. Data collection techniques are observation, interviews, and documentation. The number of informants in this study is 8 people. Data analysis techniques consist of the data reduction stage, the data presentation stage, the conclusion making stage, and the verification stage. The results of the research on 5 (five) indicators that exist in the quality of public services in Bambu Pemali village are tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), and emphaty (empathy). Based on the results of the above research, it can be concluded that the quality of service of the Bambu Pemali village office, Merauke Regency, has not been optimal in providing services to the community because there are still poor services and have not run optimally so that it has quite an effect on community satisfaction, the service is slow and not on time because the community is still confused in file management and employees are not able to provide clear information. Problems related to inadequate facilities and infrastructure at the Bambu Pemali Village Office, Merauke Regency, so that it can affect the performance of employees in providing services. Keywords : Quality, Service, Village